Developing students' worksheet based on scientific approach in cell as the system of life - Fajarianingtyas, Dyah Ayu; Akbar, Naufal Afif; Herowati, H (Biosfer: Jurnal Pendidikan Biologi, 2019)
Students worksheet scientific approach is a teaching material that contains material that teaches students to experiment by following the steps based on the scientific method. The scientific method is observed, ask, gather information, associate, and communicate. The results of observation, interview with the teachers and students found that the teacher uses the revised version of the 2013 Curriculum’s handbook of natural science for grade VII. The books contain student activities cannot be done because of the limited media available in the school. So, the teacher must make student worksheets as complementary media for student activities. Constraints experienced by teachers in learning activities with the 2013 Curriculum include limited media such as electron microscope, mount, and surgical appliance for the subject of life organization system, etc. Teachers are predominantly applying scientific steps on students at the aspect of observing, questioning, and communicating, so that students’ knowledge and skill are less optimized. This study aims to determine the feasibility of student worksheets based on the VII class scientific approach. This type of research is Research and Development (R & D) with the Four D research model consisting. The sample used was Kalianget 2 Public Middle School. The result of the research showed that feasibility of Student Worksheets based on Scientific Approach obtained very feasible category, with the percentage feasibility material of 86.11% (very feasible category), feasibility format of the 85.42% (very feasible category), feasibility display of the 85.94% (category is very feasible).